Establishing a mentorship program in rural workplaces: connection, communication, and support required - Noelle Rohatinsky; Janelle Cave; Chantal Krauter (James Cook University, 2020)
Introduction: Recruitment and retention of healthcare providers to rural workplaces is often challenging due to many factors, such as complex work environments requiring a broad skill set, minimal staffing, and limited community support and resources. Mentorship has been proposed as a strategy to encourage recruitment and retention of staff in rural workplaces. This article describes a rural-specific pilot mentorship program that was implemented and evaluated in terms of supporting rural mentorships, easing workplace transition, strengthening community connections, and encouraging recruitment and retention in rural communities. Methods: Thirty volunteer registered nurse mentors and mentees were recruited from within a western Canadian province. These individuals worked in communities with populations of less than 10 000. Mentors and mentees were matched by program coordinators based on self-identified relationship priorities and similar responses to questions including preferred frequency and method of contact. Online orientation to the program was provided and the formal mentorship lasted 4 months. Follow-up program evaluation was conducted via informal electronic feedback and comprehensive interviews that were analyzed using thematic analysis. Results: Three themes were identified by participants that serve as key considerations when implementing a rural mentorship program: connection, communication, and support. Connection describes the variety of relationships participants formed throughout the mentorship program, including connections to their mentor/mentee, themselves, their profession, colleagues, and the larger rural community. Communication includes the logistics of corresponding between mentee-mentor dyads during the program, participant communication with the coordinators of the program, and future communication about and promotion of rural mentorship programs. Support was described as interpersonal and professional assistance provided to the mentee from the mentor as well as to the mentor from the mentorship program and management. Data from the study suggest that rural-specific mentorships are effective in terms of supporting mentorships, easing workplace transition, strengthening community connections, and encouraging recruitment and retention of registered nurses in rural health care. Pervasive throughout the themes derived from the thematic analysis of interview data was the pivotal role of four key groups (mentors, mentees, the healthcare organization, and the rural community) in developing, facilitating, and sustaining mentorships in rural areas. Conclusion: Participants in this study believed that mentorship was beneficial to support healthcare providers working in rural environments. However, greater strides need to be made in terms of creating and supporting such relationships. The responsibility for mentorship resides with not only the mentor and mentee but also health organizations and rural communities. Members from all groups need to be committed and contribute to mentorship for rural mentorship programs to be successful and sustainable. Rural residents are often underserved due to insufficient numbers of healthcare professionals working in rural areas along with a limited number of services offered. The greater the numbers of healthcare professionals that can be recruited and retained within rural communities, the greater the likelihood the community residents will have timely and appropriate access to quality health services. These services can result in positive patient outcomes and greater community health.